2009
DOI: 10.1111/j.1749-6632.2009.04564.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Characterization of Distinct Human Bone Marrow–Derived MSC Subsets

Abstract: Very recently, we identified two distinct mesenchymal stem cell (MSC) subsets in primary bone marrow (BM) that differ in their expression pattern (CD271(bright)MSCA-1(dim)CD56(+) and CD271(bright)MSCA-1(bright)CD56(-)) and morphology as well as in their clonogenic and differentiation capacity. Here we analyzed the cell surface antigen expression in these subsets in more detail and compared the profiles with the expression pattern on cultured MSCs. Most of the tested antigens, including CD13, CD15, CD73, CD140b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
94
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(105 citation statements)
references
References 24 publications
6
94
1
1
Order By: Relevance
“…In the canine model we have previously shown that canine and human MSC share several characteristics, including expression of the most common MSC surface markers CD13, CD29, CD44, CD73, CD90, CD106 and CD166. 8,[26][27][28] Consistent with findings in humans and mice, canine MSC inhibit lymphocyte proliferation in a DLA-unrestricted dose-dependent fashion in mixed lymphocyte cultures. 7,8,29 Experience with canine MSC in the HCT model have yielded results similar to human trials.…”
Section: Dogssupporting
confidence: 73%
“…In the canine model we have previously shown that canine and human MSC share several characteristics, including expression of the most common MSC surface markers CD13, CD29, CD44, CD73, CD90, CD106 and CD166. 8,[26][27][28] Consistent with findings in humans and mice, canine MSC inhibit lymphocyte proliferation in a DLA-unrestricted dose-dependent fashion in mixed lymphocyte cultures. 7,8,29 Experience with canine MSC in the HCT model have yielded results similar to human trials.…”
Section: Dogssupporting
confidence: 73%
“…Color images available online at www.liebertpub.com/scd surface marker profile to av-MSCs. Both cell types lack expression of MSCA-1 and CD271, which have been suggested as markers for an especially clonogenic subpopulation of bone marrow MSCs [24][25][26][27]. While MSCA-1 and AP are known to be only expressed by bone-marrow-derived MSCs [24], the expression of CD271 has been described in a small subpopulation of av-MSCs before [17].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, additional flow cytometry analysis of the Lin − /PDGFRα + BM cells did not show expression of CD146 or CD271 (Fig. S9), both of which are established markers of human BM MSCs (27), indicating different cell surface molecule profiles for human BM MSCs and mouse Lin − /PDGFRα + BM cells. We then investigated the mechanism through which the transplanted skin graft is able to recruit Lin − /PDGFRα + cells from the BM.…”
Section: Resultsmentioning
confidence: 99%